NORMS OF PUNISHMENT: EXPERIMENTS WITH STUDENTS AND THE GENERAL POPULATION. - Bortolotti, Stefania; Casari, Marco; Pancotto, Francesca (Economic Inquiry, 2015)
Norms of cooperation and punishment differ across societies, but also within a single society. In an experiment with two subject pools sharing the same geographical and cultural origins, we show that opportunities for peer punishment increase cooperation among students but not in the general population. In previous studies, punishment magnified the differences across societies in people's ability to cooperate. Here, punishment reversed the order: with punishment, students cooperate more than the general population while they cooperate less without it. ( JEL C72, C90, Z13)